Attitudes, Teaching Styles, and Performance of Music, Arts, Physical Education, and Health Teachers - Magday, Grace; Gumilet, Gail (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the predictors of attitudes, teaching styles, and performance among MAPEH teachers in selected public secondary schools in Northern Nueva Vizcaya, Philippines. Anchored on Ajzen’s Theory of Planned Behavior and Grasha’s Teaching Styles Theory, the study investigated how demographic, professional, and contextual variables influence teachers’ instructional attitudes, teaching styles, and performance. A descriptive-correlational research design was employed involving 55 MAPEH teachers from selected large and mega-large public secondary schools. Total enumeration sampling was utilized. Data were gathered using an adapted and expert-validated questionnaire consisting of measures on teachers’ attitudes and teaching styles, while teaching performance was assessed through the 2024–2025 Individual Performance Commitment and Review Form (IPCRF). Reliability testing revealed excellent internal consistency for both the Attitude Toward Teaching Scale and the Teaching Style Scale. Descriptive statistics, Pearson-r correlation, and regression analysis were used in analyzing the data. Findings revealed that respondents demonstrated very high attitudes toward the teaching profession, students and learning, and instruction and innovation. Teachers also exhibited very high use of formal authority, personal model, facilitator, and delegator teaching styles. Most respondents achieved Outstanding teaching performance ratings. Significant positive relationships were found between teachers’ attitudes and teaching styles, indicating that positive professional attitudes contribute to adaptive and learner-centered instructional approaches. However, no significant relationships were identified between attitudes and teaching performance or between teaching styles and teaching performance. Regression analysis further showed that age significantly predicted teaching styles and teaching performance, while most demographic and contextual variables did not significantly predict attitudes, teaching styles, or performance. The study concluded that MAPEH teachers possessed strong professional competence, positive instructional dispositions, and effective teaching practices despite limited measurable differences in performance outcomes. The study recommends continuous professional development, mentoring programs, workload management, instructional innovation, and further review of the IPCRF system to better reflect instructional effectiveness. This study supports Sustainable Development Goal (SDG) 4 on Quality Education by promoting teacher competence and instructional effectiveness, as well as SDG 3 on Good Health and Well-Being through quality MAPEH instruction that promotes learners’ physical and emotional wellness. The study contributes to educational and institutional sustainability by supporting evidence-based teacher development programs, instructional improvement, and responsive educational policies that strengthen long-term teaching quality and learner development.
Keywords: Attitudes Toward Teaching; Instructional Innovation; MAPEH Teachers; Professional Development; Teacher Performance; Teaching Styles; Total Enumeration Sampling; Very High Attitudes; Very High Teaching Styles; Workplace Effectiveness